Analisis Makna Kekuatan Perempuan pada Karakter Jinda dalam Film The Empress of Ayodhaya - Tisna Adila; Murtiadi; Roynaldi Arista (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study analyzes the meaning of female power represented through the character of Jinda in the film The Empress of Ayodhaya using Roland Barthes' semiotic approach. This film was chosen because it significantly depicts the theme of female power through the construction of the main character, Jinda, who is portrayed as an active and strategic figure in facing the political conflicts of the Ayodhaya kingdom. Using a descriptive analytical qualitative research method, this study analyzes the symbolic, narrative, and visual elements in the film. Primary data was collected through observation of film scenes and in-depth interviews with informants knowledgeable about historical films and royal dramas. Secondary data included academic journals and relevant documents. Data analysis was conducted using Barthes' three levels of semiotics, namely denotation, connotation, and myth, with triangulation techniques to ensure data validity. The results show that at the denotative level, Jinda's strength is her courage and determination in facing difficulties after being forced to become queen. Connotatively, her strength is her ability to turn suffering into courage and build solidarity within the patriarchal system. And mythologically, Jinda symbolizes an eternal moral legacy and courage despite defeat. Overall, this film reveals that women's strength lies not only in their position or power, but also in their determination, sacrifice, and the legacy of courage created from suffering.